KERJASAMA KEAMANAN "JOINT IMPLEMENTATION CENTER" AMERIKA SERIKAT-RUSIA DALAM MENGHADAPI ISIS DI SURIAH - Prima Gilang Ramadhan, - (2018)
This paper aims to analyze the Joint Implementation Center's security cooperation between the United States (US) and Russia in 2016. The analysis of the security cooperation was undertaken to deal with ISIS groups as a terrorist group that posed a threat to the US and Russia in Syria. Implementation of such cooperation is carried out through collaboration of counterterrorism strategic moves. In analyzing the above issues, the theory of security cooperation, the concept of terrorism and counterterrorism is used as an analytical tool to understand the object of research, namely security cooperation between the US and Russia, as well as highlight ISIS as a group of terrorism, and counterterrorism to highlight US and Russian operational measures against ISIS. The results of the analysis explain that the US and Russian Joint Implementation Center's security cooperation is run through a decrease of tension between both parties and the ceasefire agreement as the time to implement counterterrorism operations in the field.